PENGARUH PERTUMBUHAN PENJUALAN, UMUR PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur Sektor Consumer Non-Cyclicals Sub Sektor Food and Beverage Yang Terdaftar DiBursa Efek Indonesia Tahun 2018-2022) - Andriyani, Yuli; Mu’arif, Syamsul (ITB AAS INDONESIA, 2024)
Tax avoidance cases often occur in Indonesia, especially in manufacturing companies. Many variables influence tax avoidance, but in this research the focus will be on sales growth, company age and institutional ownership of a company. This research aims to examine the influence of sales growth, company age and institutional ownership on tax avoidance (Empirical Study of Non-Cyclical Consumer Sector Manufacturing Companies in the Food and Beverage Sub Sector Listed on the Indonesian Stock Exchange 2018-2022). The method used in this research is purposive sampling. The test results show that simultaneously sales growth, company age and institutional ownership influence tax avoidance. Partial test results show that sales growth has an effect on tax avoidance. Company age partially influences tax avoidance, while institutional ownership partially has no influence on tax avoidance.